Perancangan Animasi 3d Kisah Perjalanan Isra’ Mi’raj Menggunakan Software 3DS Max Sebagai Media Pengenalan Kepada Anak Usia Dini - Nabila Ayu Ardiningsih; Andi Marwan Elhanafi; M. Taufik Batubara (Jurnal Ilmu Komputer dan Sistem Informasi, 2023)
In the era of increasingly developing technology, the advancement of multimedia technology, especially in the field of education, forces us to follow its development, one of the multimedia technologies used in education is animation, animation is used as a tool in the learning process, animation can also be used as a learning medium. interesting for early childhood education. The purpose of making this animation in 3D is to provide information about the story of the journey of Isra 'Mi'raj Prophet Muhammad SAW. By using the Frame by frame animation method this will be packaged into a video learning media for early childhood that is interesting and easy to understand.